The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5296/jee.v5i2.6847
|View full text |Cite
|
Sign up to set email alerts
|

Edible Fruit Trees Diversity in a Peri-Urban Centre: Implications for Food Security and Urban Greening

Abstract: One of the numerous sources of Edible fruits from trees in peri-uban centres are home gardens. However, there are limited research on the implication for food security and urban greening due to transient nature of farming in the cities. The aim of this study was to determine the extent of edible fruit tree (EFTs) planting in home garden in University of Port Harcourt and assess its impact on the social and physical environment as well as its contribution to food security and urban greening. Total enumeration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The inclusion of trees in food and nutrition security is fairly recent [5]. However, few studies have characterized urban food tree species diversity and composition within cities in West Africa [21,22] despite evidence that children who live in areas with high forest/tree cover enjoy greater dietary diversity and more nutritious foods [23].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of trees in food and nutrition security is fairly recent [5]. However, few studies have characterized urban food tree species diversity and composition within cities in West Africa [21,22] despite evidence that children who live in areas with high forest/tree cover enjoy greater dietary diversity and more nutritious foods [23].…”
Section: Introductionmentioning
confidence: 99%
“…Higher species composition of ethno medicinal tress in the RAs (499) may be due to the conservation measures of the residents by the cultivation and protecting of the trees. Larinde and Oladele [26] reported that the residents of the University of Port Harcourt plant and protect medicinal and fruit bearing trees in their homesteads. The culture of conserving frequently used medicinal plants in home gardens and traditional healers' premises were equally observed in south western Nigeria [27] in similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…Trees are planted around homes and public buildings, in the West African region are often those that bear tasty fruit, help to reduce excessive temperatures, and absorb air pollutants [188]. Other studies listed commonly planted trees for urban greening to include Mangifera indica, Carica papaya, Psidium guava, Cocos nucifera, Elaeis guinensis and Persia americana [194,195].…”
Section: Urban Greening and Green Technologymentioning
confidence: 99%